Gastrointestinal Leakage Detected by Serum (1→3)-β-D-Glucan in Mouse Models and a Pilot Study in Patients with Sepsis. Issue 5 (November 2016) - Leelahavanichkul, Asada; Worasilchai, Navaporn; Wannalerdsakun, Surat; Jutivorakool, Kamonwon; Somparn, Poorichaya; Issara-Amphorn, Jiraphorn; Tachaboon, Sasipha; Srisawat, Nattachai; Finkelman, Malcolm; Chindamporn, Ariya
Abstract : ABSTRACT: Gastrointestinal (GI) leakage is believed to exacerbate sepsis and new, validated markers of GI barrier performance might benefit clinical decision-making. Serum (1→3)-β-D-glucan (BG) was evaluated as a potential GI leakage marker. Serum BG was tested in several mouse models of GI leakage, including dextran sulfate solution (DSS) administration, endotoxin (LPS) injection, and cecal ligation and puncture sepsis (CLP). Serum BG titer was also evaluated in patients with sepsis and septic shock, for comparison. With 0.75% DSS administration, BG increased only after oral administration of heat-killed C. albicans, but increased spontaneously with 1.5% DSS. In the LPS and CLP models, BG increased as early as 1 h and at 12 h after LPS administration and surgery, respectively. GI leakage was confirmed by orthogonal validation methods including FITC-dextran oral administration in the DSS, LPS, and CLP models and, in the DSS model, with urine sucralose after oral administration and serum endotoxemia. IL-6 increased in parallel with serum BG. Serum BG or IL-6, at 18 h, anticipated sepsis mortality in the CLP model. Analysis of serum BG from patients with febrile neutropenic sepsis (N = 49) and febrile non-neutropenic sepsis (N = 39) demonstrated BG elevation. Patients with bacterial septic shock had serum BG titers similar to levels observed in invasive fungal disease, regardless of febrile neutropenia. Serum BG was lower in less severe cases of bacterial sepsis. Elevated serum IL-6 was associated with GI leakage and elevated serum BG. Serum BG may have potential as a sepsis/septic shock biomarker and further study in this context is warranted.